P-63 In-patient prescribing at a hospice: Transferring from paper copy to electronic prescribing. (19th November 2022) - Abbas, Syed Qamar; Saxena, Helen; Evans, Sophie; Humphrey, Sarah; Player, Lorraine
Abstract : Introduction: Drug prescribing is a potentially high-risk activity in palliative care as patients are commonly prescribed medication, including controlled drugs, for symptom management. Since the inception of our local hospice organisation, the in-patient unit has prescribed and administered medication using paper drug charts. All medication errors and near misses are reviewed through our clinical governance structure. Aims: Our clinical strategy identified a Quality Improvement Project (QIP) to investigate improving the quality of medicine documentation in the in-patient unit, improving patient safety. Methods: Research into solutions led to the setup of electronic prescribing medicines administration (ePMA) software within our existing electronic (SystmOne) electronic notes record. To support with implementation and best practice sharing, we connected with other UK hospices. The creation of a local formulary, system configuration, testing, guidance creation and contingency plans all formed part of the project prior to training all users and transitioning in April 2022. Analysis and Results: We anticipate initial increase in recording errors while the system embeds, before incidents reduce. We continue to seek feedback from users informally; remaining flexible, amending system settings to support effective and safe patient care. Pre-ePMA our prescribing and administration errors were 14 over 6 months. It is now reduced to 7 over 6 months. We will formally review our processes and errors after one month. Conclusion: This transition has been challenging, as is any process of change, particularly when including technology in the healthcare setting. We recognised the importance of allowing time for planning, testing and establishing clarity of processes prior to changing. Collaboration between the project leads and the medical and nursing teams was also important to ensure safe, high quality medication recording whilst remaining flexible, meeting our patients' complex needs. Despite staffing challenges, the change has been well received and successful due to staff's determination to support the initiative and a positive attitude to change.